Distance Learning in Higher Education - Berg, Gary A. (Education Policy Analysis Archives, 1998)
The Western Governors University (WGU) and the California Virtual University (CVU) are revealing examples of the complex issues involved in implementing distance learning on the public policy level. Although technology is certainly important, it has masked the fact that the WGU and CVU initiatives mark the rise of learner-centered higher education and the increased role of business in the academy. In comparing and contrasting WGU and CVU, it is clear that the WGU is a more radical proposition because of competency-based credit and the connection with private industry. Two important issues driving public policy are raised in these two efforts: First, are the California and Western Governors Association initiatives the product of the commercialization of education or the result of a reform of higher education that may lead to an increased learner-centered orientation? Second, what is the appropriate role of private industry in higher education?